Pendampingan Pos Bantuan Hukum (POSBAKUM) Kepada Masyarakat Kurang Mampu Dalam Konteks Equality Before The Law Di Pengadilan Agama Kabupaten Jember - Yunita Wulandari; Siti Habibah; Yulia Nisah; Siti Karomatul Ghoniyah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The presence of the Legal Aid Post (Posbakum) is generally referred to as a major invasion, representing a development of the previous government's legal aid policies. Its existence reflects Indonesia's lawful state responsibilities. The Supreme Court (MA) established Posbakum in all courts of first instance that provide legal aid services, including General Courts, Religious Courts, and State Administrative Courts. This service activity was carried out at the Jember Religious Court with the goal of providing knowledge and understanding to the people of Jember Regency, particularly the less fortunate, so that they are more aware of the Jember Religious Court's legal aid facilities, which can assist in filing or handling cases and ensuring equality before the law.